Solution:
Given:
![x^2=6y](https://tex.z-dn.net/?f=x%5E2%3D6y)
Part A:
The vertex of an up-down facing parabola of the form;
![\begin{gathered} y=ax^2+bx+c \\ is \\ x_v=-\frac{b}{2a} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3Dax%5E2%2Bbx%2Bc%20%5C%5C%20is%20%5C%5C%20x_v%3D-%5Cfrac%7Bb%7D%7B2a%7D%20%5Cend%7Bgathered%7D)
Rewriting the equation given;
![\begin{gathered} 6y=x^2 \\ y=\frac{1}{6}x^2 \\ \\ \text{Hence,} \\ a=\frac{1}{6} \\ b=0 \\ c=0 \\ \\ \text{Hence,} \\ x_v=-\frac{b}{2a} \\ x_v=-\frac{0}{2(\frac{1}{6})} \\ x_v=0 \\ \\ _{} \\ \text{Substituting the value of x into y,} \\ y=\frac{1}{6}x^2 \\ y_v=\frac{1}{6}(0^2) \\ y_v=0 \\ \\ \text{Hence, the vertex is;} \\ (x_v,y_v)=(h,k)=(0,0) \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%206y%3Dx%5E2%20%5C%5C%20y%3D%5Cfrac%7B1%7D%7B6%7Dx%5E2%20%5C%5C%20%20%5C%5C%20%5Ctext%7BHence%2C%7D%20%5C%5C%20a%3D%5Cfrac%7B1%7D%7B6%7D%20%5C%5C%20b%3D0%20%5C%5C%20c%3D0%20%5C%5C%20%20%5C%5C%20%5Ctext%7BHence%2C%7D%20%5C%5C%20x_v%3D-%5Cfrac%7Bb%7D%7B2a%7D%20%5C%5C%20x_v%3D-%5Cfrac%7B0%7D%7B2%28%5Cfrac%7B1%7D%7B6%7D%29%7D%20%5C%5C%20x_v%3D0%20%5C%5C%20%20%5C%5C%20_%7B%7D%20%5C%5C%20%5Ctext%7BSubstituting%20the%20value%20of%20x%20into%20y%2C%7D%20%5C%5C%20y%3D%5Cfrac%7B1%7D%7B6%7Dx%5E2%20%5C%5C%20y_v%3D%5Cfrac%7B1%7D%7B6%7D%280%5E2%29%20%5C%5C%20y_v%3D0%20%5C%5C%20%20%5C%5C%20%5Ctext%7BHence%2C%20the%20vertex%20is%3B%7D%20%5C%5C%20%28x_v%2Cy_v%29%3D%28h%2Ck%29%3D%280%2C0%29%20%5Cend%7Bgathered%7D)
Therefore, the vertex is (0,0)
Part B:
A parabola is the locus of points such that the distance to a point (the focus) equals the distance to a line (directrix)
Using the standard equation of a parabola;
![\begin{gathered} 4p(y-k)=(x-h)^2 \\ \\ \text{Where;} \\ (h,k)\text{ is the vertex} \\ |p|\text{ is the focal length} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%204p%28y-k%29%3D%28x-h%29%5E2%20%5C%5C%20%20%5C%5C%20%5Ctext%7BWhere%3B%7D%20%5C%5C%20%28h%2Ck%29%5Ctext%7B%20is%20the%20vertex%7D%20%5C%5C%20%7Cp%7C%5Ctext%7B%20is%20the%20focal%20length%7D%20%5Cend%7Bgathered%7D)
Rewriting the equation in standard form,
![\begin{gathered} x^2=6y \\ 6y=x^2 \\ 4(\frac{3}{2})(y-k)=(x-h)^2 \\ \text{putting (h,k)=(0,0)} \\ 4(\frac{3}{2})(y-0)=(x-0)^2 \\ Comparing\text{to the standard form;} \\ p=\frac{3}{2} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%5E2%3D6y%20%5C%5C%206y%3Dx%5E2%20%5C%5C%204%28%5Cfrac%7B3%7D%7B2%7D%29%28y-k%29%3D%28x-h%29%5E2%20%5C%5C%20%5Ctext%7Bputting%20%28h%2Ck%29%3D%280%2C0%29%7D%20%5C%5C%204%28%5Cfrac%7B3%7D%7B2%7D%29%28y-0%29%3D%28x-0%29%5E2%20%5C%5C%20Comparing%5Ctext%7Bto%20the%20standard%20form%3B%7D%20%5C%5C%20p%3D%5Cfrac%7B3%7D%7B2%7D%20%5Cend%7Bgathered%7D)
Since the parabola is symmetric around the y-axis, the focus is a distance p from the center (0,0)
Hence,
![\begin{gathered} Focus\text{ is;} \\ (0,0+p) \\ =(0,0+\frac{3}{2}) \\ =(0,\frac{3}{2}) \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20Focus%5Ctext%7B%20is%3B%7D%20%5C%5C%20%280%2C0%2Bp%29%20%5C%5C%20%3D%280%2C0%2B%5Cfrac%7B3%7D%7B2%7D%29%20%5C%5C%20%3D%280%2C%5Cfrac%7B3%7D%7B2%7D%29%20%5Cend%7Bgathered%7D)
Therefore, the focus is;
![(0,\frac{3}{2})](https://tex.z-dn.net/?f=%280%2C%5Cfrac%7B3%7D%7B2%7D%29)
Part C:
A parabola is the locus of points such that the distance to a point (the focus) equals the distance to a line (directrix)
Using the standard equation of a parabola;
![\begin{gathered} 4p(y-k)=(x-h)^2 \\ \\ \text{Where;} \\ (h,k)\text{ is the vertex} \\ |p|\text{ is the focal length} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%204p%28y-k%29%3D%28x-h%29%5E2%20%5C%5C%20%20%5C%5C%20%5Ctext%7BWhere%3B%7D%20%5C%5C%20%28h%2Ck%29%5Ctext%7B%20is%20the%20vertex%7D%20%5C%5C%20%7Cp%7C%5Ctext%7B%20is%20the%20focal%20length%7D%20%5Cend%7Bgathered%7D)
Rewriting the equation in standard form,
![\begin{gathered} x^2=6y \\ 6y=x^2 \\ 4(\frac{3}{2})(y-k)=(x-h)^2 \\ \text{putting (h,k)=(0,0)} \\ 4(\frac{3}{2})(y-0)=(x-0)^2 \\ Comparing\text{to the standard form;} \\ p=\frac{3}{2} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%5E2%3D6y%20%5C%5C%206y%3Dx%5E2%20%5C%5C%204%28%5Cfrac%7B3%7D%7B2%7D%29%28y-k%29%3D%28x-h%29%5E2%20%5C%5C%20%5Ctext%7Bputting%20%28h%2Ck%29%3D%280%2C0%29%7D%20%5C%5C%204%28%5Cfrac%7B3%7D%7B2%7D%29%28y-0%29%3D%28x-0%29%5E2%20%5C%5C%20Comparing%5Ctext%7Bto%20the%20standard%20form%3B%7D%20%5C%5C%20p%3D%5Cfrac%7B3%7D%7B2%7D%20%5Cend%7Bgathered%7D)
Since the parabola is symmetric around the y-axis, the directrix is a line parallel to the x-axis at a distance p from the center (0,0).
Hence,
![\begin{gathered} Directrix\text{ is;} \\ y=0-p \\ y=0-\frac{3}{2} \\ y=-\frac{3}{2} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20Directrix%5Ctext%7B%20is%3B%7D%20%5C%5C%20y%3D0-p%20%5C%5C%20y%3D0-%5Cfrac%7B3%7D%7B2%7D%20%5C%5C%20y%3D-%5Cfrac%7B3%7D%7B2%7D%20%5Cend%7Bgathered%7D)
Therefore, the directrix is;
![y=-\frac{3}{2}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B3%7D%7B2%7D)